Psychology’s Ghosts: The Crisis in the Profession and the Way Back by Jerome Kagan - Dineen, Tana (Journal of Scientific Exploration, 2014)
Psychology’s Ghosts—an intriguing title; Jerome Kagan—an esteemed psychologist. This combination promised a book well worth reading; my expectations were high. But my first impression was not good and I came close to giving up on it. The author bounces around from topic to topic, causing the book to read like a transcript of free associations, seemingly a product of whatever came into Kagan’s mind no matter how tangential to the topic at hand. For example, one paragraph in the first chapter reads: The distinctive emotional profiles of disadvantaged and advantaged adults affect how they socialize their children. This may be the most robust fact discovered by social scientists. Readers who broke a leg or suffered from the pain of shingles for several months will remember their helplessness and compromised sense of agency. Many adults trapped in poverty and possessing no special skills feel impotent to alter their unhappy condition. My head was left spinning. But I read on and came to appreciate that, however poorly written (or poorly edited) it was, this book does address important issues. If you can tolerate an author who jumps around from historical opinion (“the Japanese attacked the United States in 1941 because they regarded themselves as a superior race . . .”) to cultural comment (“after 1950 many American parents became excessively concerned with perfecting their child’s sense of self”); from neurobiology (“depressives who inherit the long allele of the serotonin transporter also improve more on drug therapy than depressed patients with the short allele”) to broad generalizations (“humans cannot resist inventing goals they believe they should attain”), then reading this book may be worth the effort. Kagan challenges four broad, underlying, and unfounded assumptions on which psychologists are inclined to conduct their research and build their theories. He calls these assumptions “Psychology’s Ghosts.” They’ve all been talked about, written about, and complained about for years, even decades, but Kagan takes his own, at times well-aimed, personal swing at them.